Inequality in the impact of the coronavirus shock: evidence from real time surveys - Adams-Prassl, A; Boneva, T; Golin, M; Rauh, C (Elsevier, 2020)
We present real time survey evidence from the UK, US and Germany showing that the immediate labor market impacts of Covid-19 differ considerably across countries. Employees in Germany, which has a well-established short-time work scheme, are substantially less likely to be affected by the crisis. Within countries, the impacts are highly unequal and exacerbate existing inequalities. Workers in alternative work arrangements and who can only do a small share of tasks from home are more likely to have lost their jobs and suffered falls in earnings. Women and less educated workers are more affected by the crisis.